Edukasi Kesiapan Persalinan dan Pencegahan Komplikasi pada Ibu Hamil di Wilayah Pesisir dan Kepulauan - Zubaeda Zubaeda; Suryanti Tukiman; Siti Murdani Haupea; Runi Anggriani La Amin; Asi Dwi Astuti (Pakis Journal Institute, 2026)
Island regions face various challenges in maternal health services, including limited access to healthcare facilities, shortages of health workers, transportation barriers, and geographical conditions that contribute to delays in the management of obstetric complications. This community service activity aimed to improve knowledge regarding childbirth preparedness and the prevention of pregnancy complications through education and assistance. The methods used included health education sessions and leaflet distribution to pregnant women. The target participants were pregnant women in the second and third trimesters, along with their families. The results showed an increase in pregnant women’s knowledge regarding danger signs during pregnancy, the importance of antenatal care, childbirth preparation, and emergency referral planning. This activity is expected to enhance pregnant women’s readiness for childbirth and reduce the risk of maternal complications in island areas.